2019
DOI: 10.1159/000497271
|View full text |Cite
|
Sign up to set email alerts
|

Digitalis Therapy and Risk of Recurrent Ventricular Tachyarrhythmias and ICD Therapies in Atrial Fibrillation and Heart Failure

Abstract: Objective: This study sought to assess the impact of treatment with digitalis on recurrences of ventricular tachyarrhythmias in implantable cardioverter defibrillator (ICD) recipients with atrial fibrillation (AF) and heart failure (HF). Background: The data regarding outcomes of digitalis therapy in ICD recipients are limited. Methods: A large retrospective registry was used, including consecutive ICD recipients with episodes of ventricular tachyarrhythmia between 2002 and 2016. Patients treated with digitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(47 reference statements)
0
5
0
Order By: Relevance
“…We screened the full text of the remaining 83 studies and 62 articles were excluded due to the following reasons: (a) the full text of the article could not be located ( n = 4); (b) the data of the articles were insufficient or duplicated ( n = 5); (c) the articles were off topic ( n = 42); (d) the articles were reviews or commentaries ( n = 11). Finally, 21 studies [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] encompassing 44,761 ICD or CRT-D recipients were included in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We screened the full text of the remaining 83 studies and 62 articles were excluded due to the following reasons: (a) the full text of the article could not be located ( n = 4); (b) the data of the articles were insufficient or duplicated ( n = 5); (c) the articles were off topic ( n = 42); (d) the articles were reviews or commentaries ( n = 11). Finally, 21 studies [ 10 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] encompassing 44,761 ICD or CRT-D recipients were included in this systematic review and meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The baseline characteristics of the studies included in our analysis are presented in Table 1 . Among the 21 articles, 10 studies reported the appropriate shock rate [ 10 , 13 , 14 , 18 , 21 , 22 , 24 , 26 , 30 , 32 ], 2 studies [ 13 , 16 ] reported the time to the first appropriate shock, and 14 articles reported the mortality of ICD or CRT-D recipients [ 10 , 13 , 15 , 17 , 23 , 25 , 27 , 28 , 29 , 31 , 32 ]. Six of the included articles were prospective studies and fifteen were retrospective studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps the use of digoxin heightens the risk of ventricular and atrial arrhythmias, which are known complications of digoxin. 24 While the DIG trial shows there is a reduction in death because of HF with chronic digoxin use, there was a reciprocal heightened risk of mortality attributable to arrhythmias. 15 In addition, myocardial ischemia increases the risk of fatal ventricular arrhythmias with digoxin therapy, 25 which may be problematic for patients with PAH as they are at risk for RV ischemia because of loss of right coronary artery perfusion during systole and capillary rarefaction.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, MF detection primarily occurs via imaging or measuring the expression of related biomarkers; however, biomarkers that are directly associated with MF have not been identified (7,8). Diuretics, Digitalis and angiotensin-converting enzyme inhibitors are used to delay chronic HF in clinical settings, but display side effects and are not suitable for long-term treatment (9,10). Therefore, the identification of novel drugs and therapeutic targets to delay MF and prevent HF is important.…”
Section: Introductionmentioning
confidence: 99%